Public Libraries Are Critical Partners for Collective Impact on Climate Action - Aldrich, Rebekkah (Maine Policy Review, 2024)
Public libraries exist across every state and territory in the United States and are charged with serving the public good, including community lifelong learning needs, inclusive of STEM education. In this context, the profession of librarianship has developed new thinking to articulate how public libraries can embrace the core value of sustainability, including a Na alClimate Action Strategy for Libraries. This strategy calls on public libraries to harness the transformative power of education for climate justice by developing relationships with local community organizations. This article introduces the framework that has been developedaround this topic; some of the work individual public libraries have accomplished; and points out opportunities for enhanced success of climate action plans and policies when public libraries are included.